“Geo-Polymer Technology: Unlocking The Potential For Circular Economy In Sustainable Construction” - Ms. A.A. Gosavi; Dr. M. G. Deshmukh; Ms. P.B. Ronge; Dr. M. M. Pawar; Ms.P.T. Pujari (Revista Electronica de Veterinaria, 2024)
The construction industry is a major contributor to environmental degradation, generating significant carbon emissions and waste. Geo-polymer technology has emerged as a promising alternative to traditional cement- based materials, offering a sustainable solution by utilizing industrial by-products such as fly ash, slag, and meta-kaolin. This paper explores the role of geo-polymer technology in advancing the principles of a circular economy by promoting resource efficiency, waste valorization, and reduced carbon footprint in construction. The study examines the properties, performance, and durability of geo-polymer materials compared to conventional Portland cement. Additionally, it highlights the environmental and economic benefits, including lower greenhouse gas emissions, improved material recycling, and cost-effectiveness. Through a review of recent research and case studies, this paper underscores how geo-polymer technology can revolutionize sustainable construction practices, paving the way for a resilient and eco-friendly built environment.